Hukum Administrasi Bisnis di Era Digital: Tantangan Regulasi Terhadap Platform Ekonomi Digital - Rayani Saragih; Maslon Hutabalian; Venius Ndruru; Jopia Milala (Mahesa Research Center, 2026)
This study aims to analyse the regulatory framework and implementation challenges of business administrative law in governing digital economic platforms. The research focuses on two main issues: the regulation of business administrative law concerning digital economic platforms within Indonesia’s current regulatory framework, and the key challenges in implementing business administrative law to ensure legal certainty and social justice in the digital economy. This study employs a normative juridical legal research method using statutory and conceptual approaches. The findings indicate that, at the normative level, Indonesia has established various relevant regulations to govern digital economic platforms; however, these regulations remain sectoral in nature and have not yet been integrated into a comprehensive and adaptive framework of business administrative law. The main challenges lie in administrative implementation, as reflected in fragmented institutional authority, weak inter-agency coordination, limited supervisory capacity, and regulatory instruments that are insufficiently responsive to the distinctive characteristics of digital platforms. This study concludes that strengthening business administrative law in the digital era requires reforming the design and capacity of state administrative instruments in a manner that is integrated, adaptive, and oriented toward public interest and social justice.